The Legal Position of Notary Deed in Establishing Water-Using Farmers' Associations - Ardhea Safira Prawestri; Taufan Fajar Riyanto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
The role of the Notary in the process of establishing the Association, among others, is to make a deed of Establishment of the Association and register it with the Ministry of Law and Human Rights if it is desired that the association is a legal entity. The existence of an authentic deed made by a notary is used to protect and guarantee the rights and obligations of the parties to the agreement. A normative juridical approach is used in this study, and is carried out by examining existing library materials. The results of this study are the legal position of a notary deed in the establishment of a water user farmer association in Semarang district is recognized by regulations, namely according to Act No. 16 of 2017 concerning Stipulation of Government Regulation in Lieu of Act No. 2 of 2017 concerning Amendments to Act No. 17 of 2013 concerning Social Organizations. The legal consequences that arise from the establishment of a notarized association of farmers using water will result in legal certainty for farmers in improving irrigation management independently, efficiently, and effectively.